Back to monoxeny: Phytomonas nordicus descended from dixenous plant parasites - Frolov, Alexander O; Malysheva, Marina N; Yurchenko, Vyacheslav; Kostygov, Alexei Yu (European journal of protistology, 2016)
The trypanosomatid Phytomonas nordicus parasitizing the predatory bug Troilus luridus was described at the twilight of the morphotype-based systematics. Despite its monoxenous life cycle, this species was attributed to the dixenous genus Phytomonas due to the presence of long twisted promastigotes and development of flagellates in salivary glands. However, these characteristics were considered insufficient for proving the phytomonad nature of the species and therefore its description remained virtually unnoticed. Here, we performed molecular phylogenetic analyses using 18S ribosomal RNA (rRNA) gene and region containing internal trascribed spacers (ITS) 1 and 2 and convincingly demonstrated the affinity of P. nordicus to the genus Phytomonas. In addition, we investigated its development in the salivary glands. We argue that in many aspects the life cycle of monoxenous P. nordicus resembles that of its dixenous relatives represented by tomato-parasitizing Phytomonas serpens.
Keywords: Phylogeny; Evolution; druhová specificita; DNA, Ribosomal Spacer; Monoxenous lifestyle; Phytomonas; fylogeneze; RNA ribozomální 18S; Trypanosomatina; Animals; Species Specificity; Ultrastructure; Heteroptera; zvířata; mezerníky ribozomální DNA; RNA, Ribosomal, 18S